1994
DOI: 10.1021/bi00191a021
|View full text |Cite
|
Sign up to set email alerts
|

Affinity Cleavage at the Putative Metal-Binding Site of Pigeon Liver Malic Enzyme by the Fe2+-Ascorbate System

Abstract: Pigeon liver malic enzyme was rapidly inactivated by micromolar concentrations of ferrous sulfate in the presence of ascorbate at neutral pH and 0 or 25 degrees C. Omitting the ascorbate or replacing the ferrous ion with manganese ion did not lead to any inactivation. Manganese, magnesium, zinc, cobalt, or calcium ion at 200 molar excess over ferrous ion offered complete protection of the enzyme from Fe(2+)-induced inactivation. Ni2+ provided partial protection, while Ba2+ or imidazole was ineffective in prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 38 publications
5
43
0
Order By: Relevance
“…1), i.e. in correlation with our previous observation (Wei et al, 1994 -ascorbate system between pH 4.0 -9.0 in which the enzyme was stable. There are two optima for the inactivation rate: one at pH 6.0 -7.0, and the other at approximately pH 4.0 (Fig.…”
Section: Selective Inactivation Of Pigeon Liver Malicsupporting
confidence: 92%
See 3 more Smart Citations
“…1), i.e. in correlation with our previous observation (Wei et al, 1994 -ascorbate system between pH 4.0 -9.0 in which the enzyme was stable. There are two optima for the inactivation rate: one at pH 6.0 -7.0, and the other at approximately pH 4.0 (Fig.…”
Section: Selective Inactivation Of Pigeon Liver Malicsupporting
confidence: 92%
“…Without a three-dimensional crystal structure available, affinity cleavage at the putative metal-binding site by the metal-catalyzed oxidation system (MCO) 1 may be the optimal approach of reaching the above goal. Using this technique with the Fe 2ϩ -ascorbate system, Asp 258 is successfully identified in our previous study as one of the metal-binding sites (Wei et al, 1994), as confirmed by site-directed mutagenesis (Wei et al, 1995). In that study, some divalent metal ions were found to be capable of providing protection of the enzyme against Fe 2ϩ -induced inactivation.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…The box I11 sequence is exactly the consensus between all malic and malolactic enzymes. Asp"' (second D in FNDDIQGT sequence) in pigeon liver malic enzyme is the metal coordinate (Wei et al, 1994). Four mutant enzymes substituted at Asp25s with glutamate, asparagine, lysine or alanine were inactive.…”
Section: Comparison Of Amino Acid Sequences Between Mle Fragments Andmentioning
confidence: 99%